Valuing community health workers (CHWs): Opportunity costs and out-of-pocket spending among CHWs in the Indonesian stunting prevention program - Adriana Viola Miranda; Ryan Rachmad Nugraha; Trio Sirmareza; Maritta Rastuti; Rizky Deco Praha; Rindang Asmara; Zack Petersen (Clinical Epidemiology and Global Health)
Introduction: In the Indonesian stunting prevention program, the often non-salaried community health workers (CHWs) are responsible for monthly monitoring, counseling, and home visits. Understanding the importance of their roles from an economic perspective may inform a more sustainable and improved program delivery. Aim: To estimate the opportunity costs and out-of-pocket spending incurred by the CHWs in the Indonesian stunting prevention program. Methods: This cross-sectional study was conducted in two rural villages in Lombok, Indonesia. We interviewed 130 CHWs with a pre-validated, structured questionnaire. Opportunity costs were assessed using two valuation models: calculating their working time valuation based on regional minimum wage and the CHWs’ self-reported earnings outside of their community health work. Results: We found that 52·31 % of the CHWs were not satisfied with the current incentivization scheme. Opportunity cost calculation shows that these CHWs were underpaid: reported monthly workload is valued at USD 46·54 according to the valuation model based on regional minimum wage and USD 13·81 based on CHWs self-reported income. Furthermore, out-of-pocket spending reached almost one-third of the received incentives (median USD 2.90 (IQR 0·87–4·95)). Conclusion: Appropriately incentivizing CHWs working on stunting prevention programs in Indonesia is one of the main priorities to ensure better program delivery.